AN ANALYSIS OF EUPHEMISMS FOUND IN THE POLITICAL ISSUES NEWS OF THE JAKARTA POST ONLINE NEWSPAPER - AVRIANTI, NUKE ELOK (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword : Euphemisms, Type of Euphemisms, Motives of using Euphemisms The  political  issues  which  become  the  highlighted  issues  in  media Indonesia in recent days is the reason of the writer in conducting this study. The writer wants to examine how the euphemistic expression is used in the newspaper when they publish their article. The writer analyzed the political  issues news written in The Jakarta Post online newspaper since the development of technology is running very fast so the news updates rapidly by minutes. The Jakarta Post online newspaper is used as the object in this study because this newspaper is one of the most popular English newspapers in Indonesia. There are two problems to be solved in this study, they are: (1) what types of euphemisms are found in The Jakarta Post online newspaper; and (2) what are the motives of using euphemisms in the Jakarta Post online newspaper. The writer uses Warren’s (1992) theory in analyzing the type of euphemisms and Ulmann’s (1962) for analyzing the motives. This study is using qualitative method since it needs comprehensible and methodological explanation about the analysis of euphemisms. The data are taken from the online newspaper article containing euphemisms. This study discovers that there are six types of euphemisms found in the data and  they are  understatement  or litotes,  metaphor,  metonym,  implication, reversal or irony, and compounding. The writer also analyzes the motives behind the using of euphemisms. The writer found two motives used in this study; they are delicacy fall and propriety motive. In this study, delicacy fall motive is used to avoid direct utterance about crime action and in this case is closely related to corruption  or  bribe.  Meanwhile,  the  propriety  motive  is  used  to  avoid  direct talking about sex or certain body parts, swearing, and in making the expression more polite in the communication. The writer suggests other students or future researchers who have the same interest on Sociolinguistics, especially Euphemisms, analyze the same study by using the different object and theory. For example, they may take the data from news on TV with more various issues. In addition, other researchers also may conduct the study of euphemisms by combining theories from other linguistic fields such as Semantics or Discourse Analysis.